Engajamento e desengajamento moral de docentes em formação diante de situações de bullying envolvendo alvos típicos e provocadores - Gonçalves, Catarina Carneiro (2017)
Bullying have been presented as violent ways that reach students identity building and they happen, over all, in educational ambient. Otherwise Bullying happens in peer’s relations, its prevention and overcoming demands teacher’s intervention, who need to be able of taking to students the conscientious about the moral content on the role in a victimization situation. But, for that, it is necessary that these professionals get to know the values on game in this violence and get sensitive facing it. However, we realize some teachers understand the peer’s violence process in an inappropriate form, holding the targets on bad living situations or charging responsibility of stepping in to the families. Facing that, they use moral disengagements, which through decline or even refute the problem, what turns figuring out actions to solve the situation impossible. Recognizing the problem instituted by teachers’ moral disengagement and their omission often related, we had the goal to analyze what they express, in moral development terms: its kinds, variation, and the frequency of moral engagements and disengagements, from forming teachers facing bullying situations, involving a classic target and the usual challenger. The method is defined as exploratory and the data searching tool, built and validate to this research, had two bullying fictions situations, involving an usual target and other one the challenger. To each kind of target were presented eight categories of moral disengagement, proposed by Bandura and, at the same time, two ways of moral engagement defined for this thesis. 200 studying teachers from Pedagogical course of a Federal University participated. The data were organized with SPSS software and the analysis and frequency from engagement and disengagements realized using the t-Student paired test. To correlate them, it was used the McNemar test and it analysis and validation of the model used the Main Component Analysis. The data indicate bigger involvement from teachers’ moral engagement mechanisms by social convention, followed by Moral Disengagement without moral values denial. It still indicates that, there are no differences between the moral engagement or disengagement mechanism depending on the target type, otherwise the frequency has been higher when it is related to the usual target. The more presented Moral Disengagements were Passing the Responsibility Away or Blaming Someone. This thought realized, also, a moral heteronomy among teachers, which were located priority in levels two and three of Moral Development here stablished. On final considerations, there were presented for teachers beggining and continued formation, valorizing the school and its culture as important training spaces for overcoming values that support the Moral Disengagement and for moral and autonomy achievements by teachers.